Analysis of microbial aerosols diversity in cattle farms in Ningxia - Guo, Yanan; Mao, Yanni; Zhao, Shuqiang; Yang, Fei; Yu, Youli; Chen, Chong; Yang, Mengmeng; Wang, Jiandong (Frontiers in Veterinary Science, 2025)
IntroductionBeef cattle farming, a key industry in Ningxia Hui Autonomous Region, has intensified, raising public health concerns due to bioaerosol emissions. However, the distribution characteristics of these bioaerosols remain poorly understood.MethodsWe characterized bacterial communities in bioaerosols from beef cattle pens across five Ningxia regions—Guyuan (G), Yinchuan (Y), Shizuishan (S), Zhongwei (Z), and Wuzhong (W)—and compared two rearing scales: smallholder farms (S) and large-scale farms (L). Using filter membrane sampling and 16S rRNA gene sequencing, we analyzed bacterial abundance and diversity.Results and DiscussionRegional differences significantly influenced bacterial abundance (p < 0.05), whereas rearing scales had minimal impact. We identified 45,486 operational taxonomic units (OTUs), of which 423 were shared across all samples, constituting a core microbiome that accounted for 46% of total sequences. Co-occurrence network analysis revealed greater microbial interaction complexity in regionally distinct samples. Our results elucidate the distribution of bioaerosol-borne microbial communities in cattle farms, highlighting potential transmission pathways of airborne microorganisms and informing strategies to mitigate exposure risks for livestock and workers.